Does a slump really make you thinner? Finnish micro-level evidence 1978 - 2002 - Petri Böckerman (The Research Institute of the Finnish Economy (ETLA), 2004)
This study explores the relationship between obesity and economic conditions in Finland, using individual microdata from 1978 to 2002. The results reveal that an improvement in regional economic conditions measured by the employment-topopulation ratio produces a decrease in obesity over the period of investigation, other things being equal. This effect arises from the decline in the height-adjusted weight of people who are deeply overweight (BMI>35). In addition, the effect is strongest for the people in later middle age (aged 45-65). The incidence of obesity is unrelated to the regional growth rate. All in all, the Finnish evidence presented does not support the conclusions reported by Ruhm (2000, 2003, 2004) for the USA, according to which temporary economic slowdowns are good for health. In contrast, at least overweight increases during slumps. – overweight ; business cycles ; health – – Tutkimuksessa tarkastellaan ylipainon ja talouden tilan välistä yhteyttä Suomessa vuosina 1978-2002 käyttäen mikroaineistoa. Tulosten mukaan alueen työllisyysasteen nousu johtaa väestön liikalihavuuden vähenemiseen. Vaikutus syntyy huomattavasti ylipainoisten (BMI-indeksi > 35) painon vähenemisestä. Lisäksi vaikutus on suurempi myöhemmässä keski-iässä oleville (46-65-vuotiaat). Ylipainon yleisyys on riippumaton alueen talouskasvusta. Suomea koskevat tulokset eivät ole sopusoinnussa Ruhmin (2000, 2003, 2004) Yhdysvalloille raportoimien havaintojen kanssa, joiden mukaan tilapäiset taantumat talouskasvussa ovat hyväksi ihmisten terveydelle. Tulosten valossa ainakin ylipaino-ongelma pahenee talouden taantumien aikana. – ylipaino ; suhdanteet ; terveys
Keywords: E32; I12; R11; 330